THE SOLUTION OF THE SPACE FRACTIONAL SCHRÖDINGER EQUATION BASED ON NON-SINGULAR CAPUTO-FABRIZIO DERIVATIVE - BOUZENNA FATMA EL-GENBAZIA; MEFTAH MOHAMMED TAYEB (University Of Eloued جامعة الوادي, 2020)
In this work, we solve the space fractional Schr odinger equation based on non singular Caputo-Fabrizio derivative de nition for 1D linear potential. To reach this goal, we rst work out the fractional di erential equation de ned in terms of Caputo-Fabrizio derivative. Hence, the wave functions of fractional Schr odinger equations are derived.
Intervention
Keywords: SPACE FRACTIONAL SCHRÖDINGER; EQUATION BASED ON NON-SINGULAR; EQUATION BASED ON NON-SINGULAR CAPUTO-FABRIZIO DERIVATIVE